Retórica de los sentimientos : etnografías amerindias - Gutiérrez Estévez, Manuel; Surrallés, Alexandre (Madrid : Iberoamericana ; Frankfurt am Main : Vervuert, 2015)
"It offers an ethnographic approach to contemporary Amerindian emotions, a winding route that goes from the relationship between perception and affection to class actions, political, cultural recognition, through the study of their rituals and social contexts in general, besides attending in all cases, the link between emotion and textual rhetoric" --Google.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Emotions -- Anthropological aspects; Indigenous peoples -- Latin America; Emociones -- Aspectos antropológicos.; Pueblos indígenas -- América Latina; Libros electrónicos.